2022
DOI: 10.1186/s40798-021-00374-y
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Prescription Medications and Their Effect on Athletic Performance: A Systematic Review and Meta-analysis

Abstract: Background Stimulant medications used for the treatment of Attention Deficit-Hyperactivity Disorder (ADHD) are believed to provide a physical advantage in athletics, but several of these medications are not regulated by the World Anti-Doping Association. Given the prevalence of ADHD among the athlete population and concern for abuse of ADHD medications, this review and meta-analysis aimed to evaluate effects of ADHD medications on athletic performance, thereby appraising the validity of claims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…The Cochrane Collaboration tool was used by 2 authors(JL,WYL) to evaluated the quality of the studies independently [ 19 , 20 ]. Seven specific domains was addressed in Cochrane Collaboration tool, namely: random sequence generation; incomplete outcome data; allocation concealment; blinding of outcome assessment; blinding of participants and personal; selective reporting; and other issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cochrane Collaboration tool was used by 2 authors(JL,WYL) to evaluated the quality of the studies independently [ 19 , 20 ]. Seven specific domains was addressed in Cochrane Collaboration tool, namely: random sequence generation; incomplete outcome data; allocation concealment; blinding of outcome assessment; blinding of participants and personal; selective reporting; and other issues.…”
Section: Methodsmentioning
confidence: 99%
“…If I 2 > 50% and P < 0.5, has high test heterogeneity, and the random effects model is employed. When the results are similar, the random effect model is preferred, because some researchers believe that the random-effect model is a more natural choice than the fixed effect model in medical decision-making [ 19 , 22 ]. The fixed‐effect model and 95% CI [ 23 , 24 ] was used to analysis the results of the comparative tests.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 25-78% of adults with ADHD show positive response rates with stimulant medication (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022) and treatment has been shown to sustain and improve attention, inhibition control, cognitive flexibility, planning, verbal learning, on-task behavior, and cognitive performance (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022). The most prescribed medications for ADHD are amphetamines (A; i.e., Adderall, Vyvanse) and methylphenidate (MPH; i.e., Concerta, Ritalin) (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022). Immediate-release formulations allow for multiple doses within the day (four maximum) and last up to 3-4 h (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022).…”
Section: Pharmacology Of Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…The most prescribed medications for ADHD are amphetamines (A; i.e., Adderall, Vyvanse) and methylphenidate (MPH; i.e., Concerta, Ritalin) (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022). Immediate-release formulations allow for multiple doses within the day (four maximum) and last up to 3-4 h (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022). Extended-release formulations allow for one dose that releases the medication throughout the day with effects lasting 6-10 h (Smith, 2003;Minzenberg, 2012;Volkow and Swanson, 2013;Chabreck, 2015;Stewman et al, 2018;Berezanskaya et al, 2022).…”
Section: Pharmacology Of Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
See 1 more Smart Citation